(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Ear infection is a common problem for both children and adults especially in developing countries. However in Bangladesh particularly in the study area, there is no recent data that shows the magnitude of the problem. A retrospective study was conducted from from April, 2013 to March, 2014 at Shaheed Monsur Ali Medical College. Ear discharge samples were cultured on MacConkey agar, blood agar and chocolate agar plates. A total of 115 ear discharge samples were tested for bacterial isolation and 86 (74.78%) cases were found positive; 49 (56.98%) were gram negative bacteria and the predominant isolate were S. aureus 21 (24.42%) followed by Pseudomonas aeruginosa 20 (23.26%). Of individuals 70 (81.40%) had single bacterial infection and 16 (18.60%) had mixed bacterial infections. Under five children were more affected by ear infection. The prevalence of ear infection was higher in females than males (64.35% vs 35.65%) (P=0.879). The prevalence of ear infection was very high in the study area. Majority of the bacterial isolates were resistant to multiple antibiotics. Hence antibiotics susceptibility test is mandatory before prescribing any antibiotics. Bangladesh J Med Microbiol 2015; 9 (2): 20-23